2020
DOI: 10.1021/acsnano.0c04403
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Materials for Energy-Efficient Spin–Orbit Torque Devices

Abstract: Spin−orbit torques (SOTs), which rely on spin current generation from charge current in a nonmagnetic material, promise an energy-efficient scheme for manipulating magnetization in magnetic devices. A critical topic for spintronic devices using SOTs is to enhance the charge to spin conversion efficiency. Besides, the current-induced spin polarization is usually limited to in-plane, whereas out-of-plane spin polarization could be favored for efficient perpendicular magnetization switching. Recent advances in ut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 91 publications
(189 reference statements)
1
46
1
1
Order By: Relevance
“…To have better energy efficiency, a material with a large effective θ SHA and high conductivity is very crucial to reduce the current density and energy-efficient of magnetization switching. [23][24][25][26][27] A remarkable progress of manipulating the magnetization has been made towards energy-efficiency scheme using such as alloying HM, [11,28] ferrimagnetic-rearearth transition metal alloy, [29][30] two-dimensional van der Waals materials, [31][32][33] and topological insulators (TIs). [1,27,34] Studies have shown that most TI thin films have limited electrical conductivity in the order of ≈10 5 Ω −1 m −1 , [27,34] which is several times lower than that of HMs and their alloys.…”
Section: Tuning the High-efficiency Field-free Current-induced Deterministic Switching Via Ultrathin Ptmo Layer With Mo Contentmentioning
confidence: 99%
“…To have better energy efficiency, a material with a large effective θ SHA and high conductivity is very crucial to reduce the current density and energy-efficient of magnetization switching. [23][24][25][26][27] A remarkable progress of manipulating the magnetization has been made towards energy-efficiency scheme using such as alloying HM, [11,28] ferrimagnetic-rearearth transition metal alloy, [29][30] two-dimensional van der Waals materials, [31][32][33] and topological insulators (TIs). [1,27,34] Studies have shown that most TI thin films have limited electrical conductivity in the order of ≈10 5 Ω −1 m −1 , [27,34] which is several times lower than that of HMs and their alloys.…”
Section: Tuning the High-efficiency Field-free Current-induced Deterministic Switching Via Ultrathin Ptmo Layer With Mo Contentmentioning
confidence: 99%
“…Recent years, emerging studies were carried out on 2D SOT devices. Liu et al have summarized the recent progress of SOT studies based on transition-metal dichalcogenides (TMDs) and show how these results are in line with the symmetry arguments (Liu and Shao, 2020). Husain et al reviewed the current progress in research on 2D TMDs for generating SOTs in spin-logic devices (Husain et al, 2020b).…”
Section: Introductionmentioning
confidence: 97%
“…As research interests in SOT devices based on vdW materials have increased, several excellent reviews have summarized recent work of SOT in vdW materials, [ 47 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ] in which nonmagnetic vdW materials, such as, TMDs, TIs, and graphene, are mainly used as the spin current source or spin channel. In addition, magnetic vdW materials appear as promising candidates in SOT devices.…”
Section: Introductionmentioning
confidence: 99%